JAPANEDU Volume 4 Issue 2, December 2019 FULLTEXT - JAPANEDU, Editor in Chief (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
JAPANEDU FULLTEXT Vol. 4 Issue 2 December 2019 including Front Cover, Table of Contents, and Back Cover